Online High School Community Health Worker Curriculum: Key Strategies of Transforming, Engagement, and Implementation - Zheng, Jinjie; Williams-Livingston, Arletha; Danavall, N'Dieye; Ervin, Christopher; McCray, Gail (Frontiers in Public Health, 2021)
Background: Ample research evidence has demonstrated that Community Health Worker (CHW) programs are a cost-effective, culturally integrated, and impactful way to improve community health. Although most existing CHW programs recruit adults as CHWs, high school students, with their intellectual readiness and intimate community knowledge, also have great potential to be engaged as CHWs and impact community health. In such a context, the High School Community Health Worker Curriculum (HSCHW) was created for face-to-face training in 2016 at Morehouse School of Medicine (MSM) as an innovative solution to improve community health in underserved urban neighborhoods. During the inaugural training, more than 150 inquiries nationwide were received concerning opportunities to participate in the program or replicate the curriculum. Hence, in 2018 a corresponding online curriculum was created to meet the increasing needs and increase HSCHW training flexibility. As of February 2021, 346 high school community health workers have participated in this online curriculum. Purpose: The purpose of this paper is to report the research study of the critical processes and strategies of transforming, engaging, and implementing the Online HSCHW curriculum. Method: The project team conducted the research study to identify the key strategies to transform the face-to-face HSCHW curriculum, the engagement strategies embedded in the online curriculum content development, the critical concept of interestingness in the online curriculum, curriculum implementation strategies, and curriculum outcomes. Altogether 265 students’ learning outcomes in tandem with 17 high school students’ focused-group interviews and responses to online surveys were analyzed and reported in this mixed-method study. Results: The results showed that integrating instructional design processes is critical for the online curriculum success, and the latent concept of "interestingness" embedded in the online HSCHW curriculum is effective to engage high school students in learning the complex community health worker skills through digital contents and activities. Impacts: The paper provides a short research report on the key strategies and processes of creating an engaging, effective, and scalable online community health worker curriculum for high school students.